Uninsured immigrant and refugee children presenting to Canadian paediatric emergency departments: Disparities in help-seeking and service delivery - Rousseau, Cécile (Pulsus Group Inc, 2013)
INTRODUCTION: Access to health care for medically uninsured immigrant and refugee children is a public health concern due to the consequences of delayed or substandard care for child development and health. OBJECTIVE: To explore possible differences in help-seeking and service delivery across migratory statuses, institutions and provinces. METHODS: A review was undertaken of 2035 emergency files of immigrant, refugee and undocumented children without provincial health care coverage who sought care at three major paediatric hospitals in Montreal (Quebec) and Toronto (Ontario) during 2008 and 2009. RESULTS: Refugee claimant children with Interim Federal Health Program benefits consulted for less urgent problems than the overall hospital population, except in one hospital that had a multicultural paediatric ambulatory clinic. Undocumented children and new permanent resident immigrant children within the three-month waiting period for provincial health care coverage were over-represented in the very urgent triage category and presented more often for injuries, trauma and mental health problems than did refugee claimant children. DISCUSSION/CONCLUSIONS: Wide interhospital differences suggest that the predicament of limited access to health care of these groups of vulnerable medically uninsured children needs to be addressed through further research to inform policies and develop training.